(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This literature review discusses modern risk factors contributing to the development of atherosclerosis, one of the most significant healthcare issues today. The results of experimental and clinical studies are analyzed, and their findings are discussed in the context of existing knowledge. Special attention is given to data obtained from male ApoE-deficient mice, where it has been established that the glucagon-like peptide-1 receptor agonist, Exenatide-4, improves atherosclerosis by activating the secretion of myeloid suppressor cells in the bone marrow and peripheral blood. Additionally, other factors are considered, such as apolipoprotein L1 and the consequences of brain ischemia, leading to sustained activation and increased regulation of adhesion molecules like VCAM1. The increase in aging of peripheral endothelial cells observed up to 4 weeks post-stroke and the prevalence of atherosclerosis in the carotid arteries in elderly individuals is also discussed. The work emphasizes the use of single-cell RNA sequencing (scRNA-seq) as a method for studying atherosclerosis progression. Furthermore, questions are raised about the influence of dietary traditions and comorbid conditions, such as the combination of atherosclerosis with diabetes and thyroid diseases.